Knee Extension Strength and Hamstrings-to-Quadriceps Imbalances in Elite Soccer Players - Bogdanis, G.C.a; Kalapotharakos, V.I.b (International Journal of Sports Medicine, 2015)
{This study examined the relationship between hamstrings-to-quadriceps strength ratio (H:Q) and relative strength of the knee extensors in elite soccer players. Peak torque was measured during isokinetic knee extension/flexion at angular velocities of 60°·s-1, 180°·s-1 and 300°·s-1. 18 professional players were divided into 2 groups, depending on their H:Q at 60°·s-1. Players in the lower H:Q group (n=7) had significantly smaller H:Q ratios compared with the higher H:Q group (n=11) at all angular velocities (60°·s-1: 49.2%; 95% CI: 61.3-57.8% vs. 59.5%; 95% CI: 52.2-46.2%